Can Yucca schidigera be used to enhance the growth performance, nutrient digestibility, gut histomorphology, cecal microflora, carcass characteristic, and meat quality of commercial broilers raised under tropical conditions - Alghirani, Mohamed M.; Lim, Eric Teik Chung; Mohd Sabri, Danial Shah; Mohd Tahir, Muhammad Nasir Jalaluddin; Abu Kassim, Nafeesa; Kamalludin, Mamat Hamidi; Nayan, Nazri; Abdullah Jesse, Faez Firdaus; Sazili, Awis Qurni; Loh, Teck Chwen (Multidisciplinary Digital Publishing Institute, 2021)
This study aims to study the effect of Yucca shidigera as a phytobiotic supplementation in enhancing the production performance of commercial broilers reared under tropical environments. A total of 300 male day-old Ross 308 broiler chicks were randomly allocated into six treatment groups. Treatment 1 broilers were fed with commercial diets without antibiotics. Treatment 2 broilers were fed with commercial diets added with 100 mg/kg oxytetracycline antibiotic. Treatment 3, 4, 5, and 6 were fed with the same commercial diets added with 25, 50, 75, and 100 mg/kg Y. shidigera, respectively, without antibiotic. Throughout the six weeks study period, body weight and feed intake were recorded weekly for each replicate to calculate the body weight gain and feed conversion ratio. In addition, the nutrient digestibility, gut histomorphology, cecal microflora population, carcass characteristics, and meat quality were determined. The results showed significant differences (p < 0.05) in the growth performance, apparent ileal nutrient digestibility, gut histomorphology, carcass traits, and meat quality. Overall, T6 broilers supplemented with 100 mg/kg Y. shidigera demonstrated the best production performances as compared to the other treatment broilers. In summary, information from this study will be valuable for the usability of Y. schidigera, which could be developed as a feed additive to replace antibiotics in the poultry sector in the tropics.